Suporte ao Desenvolvimento e Uso de Componentes Flexíveis - Pereira e Silva, Ricardo; Price, Roberto Tom (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1999)
Component-oriented development is being stimulated by the availability of devices allowing component interoperability, regardless of programming language, running platform and executing location. However, there are some unsolved problems concerning search and selection, functionality understanding and adaptation of components. Flexibility is an important feature for increasing component reusability. Some approaches like wrappers, help in adapting actual components to systems not fully compatible. In this paper we propose to develop components as object-oriented frameworks. This leads to flexible components, much more suitable to reuse. On the other hand, this approach makes more complex the development and the use of components. SEA is an environment supporting development and use of reusable software artifacts. It employs a describing approach like those used in OOAD methodologies. The environment supports development, semantic checking and semi-automatic translation of design specifications. In this paper we describe how SEA supports the development and the use of flexible components.